Case report: Fundic gland polyps caused by long-term omeprazole use in a Maltese dog - Lee, Haemin; Kim, Sanggu; Lee, Dohee; Chae, Yeon; Yun, Taesik; Yang, Mhan-Pyo; Kang, Byeong-Teck; Kim, Soochong; Kim, Hakhyun (Frontiers in Veterinary Science, 2023)
Long-term use of proton-pump inhibitors use can induce fundic gland polyps in the human stomach. However, this phenomenon has not been described in the veterinary literature. A 5-year-old intact female Maltese dog was referred to our hospital with chronic intermittent vomiting. The dog had been administered omeprazole (0.7-1.0 mg/kg PO q24 h) for the management of hydrocephalus for over 4 years; the omeprazole dose was increased to 10 mg/kg PO q24 h 8 months prior to presentation at referring hospital. Abdominal ultrasonography revealed marked thickening of the gastric wall with multi-lobulated, thickened folds. Subsequent endoscopy revealed marked polypoid lesions, and histological examination of the biopsy samples was consistent with the fundic gland polyps associated with proton-pump inhibitor use in humans. The lesions resolved after cessation of omeprazole, as assessed by ultrasonography. This report describes a case of fundic gland polyps following the long-term administration of omeprazole in a dog.